2018
DOI: 10.2478/prilozi-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Community-Acquired Sepsis in Adult Patients: A Six Year Observational Study

Abstract: Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to an infection and it is a major cause of morbidity and mortality worldwide. The aim of this study is to describe epidemiology of community-acquired sepsis in the Intensive care unit (ICU) of the Macedonian tertiary care University Clinic for Infectious Diseases. A prospective observational study was conducted over a 6-year period from January, 2011 to December, 2016. All consecutive adults with community-acquired s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…After searching the electronic databases, 18001 publications were retrieved. Following thorough examination according to the inclusion and exclusion criteria, 10 studies (35712 patients in total) published between 2012 and 2021 were finally included in the meta-analysis[ 4 , 6 , 9 , 11 , 12 , 19 - 23 ]. A PRISMA flow chart of the study is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After searching the electronic databases, 18001 publications were retrieved. Following thorough examination according to the inclusion and exclusion criteria, 10 studies (35712 patients in total) published between 2012 and 2021 were finally included in the meta-analysis[ 4 , 6 , 9 , 11 , 12 , 19 - 23 ]. A PRISMA flow chart of the study is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are reported in Table 1 . Of the ten included studies, five studies were conducted in the United States[ 4 , 6 , 11 , 12 , 22 ] and the remaining five studies were from the Republic of China[ 9 ], Macedonia[ 19 ], France[ 20 ], Israel[ 21 ] and Japan[ 23 ]. Three of the studies were prospective studies[ 4 , 19 , 20 ] and the other seven were retrospective studies[ 6 , 9 , 11 , 12 , 21 - 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One retrospective study included 22,354 sepsis patients found that COPD was associated with 60-day mortality [6]. On the contrary, a number of multicenter studies had reported that COPD is not the risk factor associated with hospitalized mortality in septic patients [7][8][9][22][23][24].…”
Section: Introductionmentioning
confidence: 99%